The Effect of Compensation and Work Discipline on Employee Performance (Case Study at Enseval Putera Megatrading Company - Subandri, Subandri; Putra, Wahyu Gibbran Dwi (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
In Companies and organizations, performance is an important thing that must be achieved by every employee in any company because performance is a picture of the work results of employees who have done well and productively. The purpose of this study was to determine the effect of compensation and work discipline on the performance of employees at Enseval Putera Megatrading Company. This type of research is a quantitative research, as many as 55 respondents Enseval Putera Megatrading Company. Data was collected by distributing questionnaires to respondents. Data analysis using multiple linear regression model.The results showed that compensation has a positive and significant effect on the performance of employees at Enseval Putera Megatrading Company. That is, the better the compensation, the employee’s performance will increase. Work discipline has a positive and significant effect on the performance of employees of Enseval Putera Megatrading Company. That is, the higher the work discipline, the employee’s performance will increase. Compensation and work discipline have a positive and significant effect on the performance of employees of Enseval Putera Megatrading Company. That is, the better the compensation and the higher the work discipline, the higher the employee’s performance.